Análisis del uso del hipertexto dentro del buscador Google como herramientas para estudiantes. - Estrella Moreira, Héctor Alexander (2017)
This article describes the use of hypertext in the Google browser for educational purposes. In Google you can find educational, entertaining, informative or musical information with digital content with better reception for its creative quality and clarity explanatory. Today millions of people around the world are using Google, obtaining information and acquiring knowledge. One of its major benefits is to provide a wide range of choices for education where they can constantly interact at any time with different type of information, but this wealth of information can be confusing when forming critical thinking about a specific topic due to lack of positioning on endless content. The importance of reading in academia is evident; and the use of new Information Technology and Communication (ICT) is a major contribution in the field of teaching and learning. In this regard, Google and hypertext take an innovative position within the educational field by providing a different dynamic than the conventional one, leading students to opt for a faster way to get information within the reach of a click.